Tundrostepnye gruppirovki nasekomykh i rekonstruktsiy klimata pozdnego pleistotsena nitsoviy Kolymy (Tundra-steppe insect assemblages and reconstruction of Late Pleistocene climate in lower reaches of the Kolyma River, in Russian) - Alfimov, A. V.; Berman, D. I.; Sher, A. V. (Nauka, 2003)
July and January temperatures for certain periods of the Late Pleistocene were reconstructed by Mutual Climatic Range (MCR) analysis based on 18 modern steppe and tundra species of insects, recorded in various combinations in fossil faunas of the Kolyma Lowland. Two fossil assemblages come from the sediments dated about 45000 and 35000 years ago (Karginian Interstadial), two more - from sediments of the Sartanian Glaciation stage (16000-17000 and 13000-14000 years respectively). The reconstructed summer air temperatures appear higher than modern by 1.0^.5°C in Karginian times (12.0-15.5°C) and by 1.0-2.5° in the Sartanian (12.0-13.6°C). The reconstructed range of January air temperatures is shifted towards higher values as compared to the modern; it is shown, that the MCR method reconstructs winter temperatures less adequately than summer ones. At July average temperature of about 13-14°C (that now corresponds to sparse taiga forest), joint occurrence of steppe and tundra insect species on the Arctic lowlands in the Late Pleistocene was possible only under extremely continental climate. That climate must have provided sharper temperature gradients between soil and air than today, and high contrast in thermal and moisture conditions between different units of mesoand micro-scale topography. The results confirm that during the Pleistocene, peculiar conditions of climate and landscape may have existed (usually named tundra-steppe) that supported non-analogue plant and animal communities. Our results also allow us to define boundary air temperature conditions under which those communities could exist. Communities of tundra-steppe type evolved in glacier-free continental areas of northeastern Asia as early as in the beginning of the Pleistocene.